Endovascular treatment for distal basilar artery occlusion stroke - Song, Jiaxing; Yu, Zhou; Wang, Jian; Luo, Xiaojun; Du, Jie; Tian, Zhengxuan; Yang, Shunyu; Xie, Weihua; Peng, Yuqi; Mu, Jinlin; Zi, Wenjie; Huang, Shuchun; et al. (Frontiers in Neurology, 2022)
Background This study aimed to investigate the clinical outcomes of endovascular treatment (EVT) for distal basilar artery occlusion (BAO) and compare them with the outcomes of standard medical treatment (SMT) in daily clinical practice. Methods Patients with distal BAO enrolled in the BASILAR study from January 2014 to May 2019 were included. Differences in clinical outcomes were analyzed using Pearson's chi-square test and multivariable logistic regression. Clinical outcomes were evaluated using the modified Rankin Scale (mRS) score at 90 days, the mortality at 90 days, and the occurrence of symptomatic intracranial hemorrhage within 48 h. Results Among the 267 patients with distal BAO (222 patients in the EVT group and 45 patients in the SMT group), compared with the SMT group, the EVT group was associated with a favorable outcome (mRS 0–3; 40.1 vs. 15.6%; aOR 5.44; 95% CI, 1.68–17.66; P = 0.005) and decreased mortality (44.6 vs. 71.1%, aOR 0.32, 95% CI, 0.13–0.77; P = 0.012). In the EVT group, multivariable analysis showed that the initial National Institutes of Health Stroke Scale (NIHSS) score and posterior circulation-Alberta Stroke Program Early CT Score (pc-ASPECTS) were associated with favorable functional outcomes and mortality. Conclusion Our study suggests that, compared with SMT, EVT is technically feasible and safe for patients with distal BAO.